CO₂ reduction potentials through the market expansion and lifetime extension of used cars - Yuya Nakamoto (Journal of Economic Structures, 2017)
This study develops an automobile life-cycle analysis framework considering lifetimes of new and used passenger cars. Using the analysis framework based on the Weibull survival distributions of new and used cars, I addressed the question of how the market expansion and lifetime extension of used cars affect life-cycle CO2 emissions through the entire economy. The results show the following. Under the benchmark lifetime function, a 10% increase in the market share of used cars under benchmark average new vehicle lifetime of 11.50 years yields 16.9 million tons of CO2 reduction in the cumulated life-cycle CO2 emissions during 1993-2014. I further found that a combined policy of vehicle lifetime extension and market expansion of 'used' cars can contribute toward a low-carbon transition society. I conclude that modifying the demand policy with a focus on 'used' cars with higher fuel efficiency, as well as setting a target car age of used cars, would be environmentally beneficial.
Keywords: 330; Passenger cars; Used car; Weibull survival distribution; Car replacement; Life-cycle CO2